Prognostic role of an inflammation scoring system in radical resection of oral squamous cell carcinoma - Meng Wu; Pu Ye; Wei Zhang; Hong Zhu; Huiming Yu (BMC, 2022)
Abstract Background Inflammatory markers can influence the postoperative prognosis and outcome of malignant tumors. However, the role of inflammatory factors in oral squamous cell carcinoma (OSCC) are still debatable. The primary objective of this investigation was to detect the preoperative blood fibrinogen and neutrophil-lymphocyte ratio (NLR) in OSCC patients and to determine the predictive validity of F-NLR (combined fibrinogen and NLR score). Methods A total of 365 patients with oral cancer after surgery were separated into three classes: F-NLR of 2, with hyperfibrinogenemia (> 250 mg/dL) and high NLR (> 3.2); F-NLR of 1, with only one higher index; and F-NLR of 0, with no higher indices. Univariate and multivariate analyses were used to identify risk factors for the demographic and clinical characteristics of patients in the three F-NLR groups. Kaplan-Meier survival analysis was used to assess the prognosis. Results Preoperative F-NLR showed a relatively better predictive role in oral cancer prognosis than fibrinogen and NLR alone. Multivariate analysis revealed that F-NLR has the potential to be an independent predictor for OSCC cancer-specific survival (P < 0.001). Patients with high scores had a relatively poorer prognosis than those with low scores (P < 0.001). Conclusions Our findings indicate that blood F-NLR may serve as an independent prognostic factor in OSCC patients.